Freeze-dried candies from blackcurrant (Ribes nigrum L.) and yoghurt. Physicochemical and sensorial characterization - Archaina, Diego Alberto (2019)
The objective of this work was to develop lyophilized berry candies in order to offer a healthy alternative to traditional candies. Two formulations were developed based on blackcurrants, yoghurt and different sweeteners: honey/isomalt (F1, oriented to children); and isomalt/stevia (F2, oriented to adults). F1 showed higher water content and aw values than F2; F1: 2.93 ± 0.19 (g H2O/100g sample) and aw 0.36 ± 0.06; F2: 1.79 ± 0.16g H2O/100g sample and aw 0.27 ± 0.06. Both formulations presented a pink color (F1: a* = 23.06 ± 3.18, b* = 4.35 ± 1.07; F2: a* = 35.42 ± 2.08, b* = 1.14 ± 0.88), however F2 lightness (41.03 ± 1.37) was much higher than that of F1 (15.31 ± 2.42). According to a qualitative sensory test, about 80% of the consumers described good attributes of the candies. A quantitative sensory test was used to describe textural attributes. The panel members identified texture changes along storage, mainly a decrease of hardness and crunchiness. The antioxidant activity input of both formulations was similar to that of kiwifruit and apple (F1: 4.53 ± 0.59 and F2: 4.24 ± 0.29 mmol Trolox/Kg), which is a positive feature, given that usually candies have reduced or null input of bioactive compounds.